Perfil sorológico contra Rickettsia spp e Leptospira spp e infestação de carrapatos em suínos mantidos sob diferentes sistemas de criação - Osava, Carolina Fonseca (2016)
The various types of pig farming, intensive and extensive, expose them to pig parasites but also to those from the environment of the breeding site. In this work was evaluated the exposure of bigs bred in technified farms, SISCAL (intensive breeding system in pens) and not technified (backyard) to leptospira, ticks and rickettsiae. Blood sera were analyzed to determine titers of antibodies anti-Leptospira by SAM technique and antibodies anti-rickettsial by IFA, pigs were inspected for ticks and in their breeding environment and surrounding areas (pastures and riparian vegetation), ticks were collected by the flannel dragging technique. In the farms of pigs 10.4% had anti-Leptospira antibodies, followed by SISCAL (8%) and backyard animals (2.5%). The serovars found were Bratislava, Pomona, serovar, Canicola and Icterohaemorrhagiae. Higher percentage of properties with pigs raised outdoors (SISCAL) had tick infested animals (20%) than those raised in backyard (6.7%), while commercial farms had no infested pigs nor infested breeding place. In both SISCAL and backyard pig breeding properties ticks were observed at the breeding site environment. Tick infestations were detected in areas surrounding pig breeding site in all three husbandry suystems. Ticks found were all Amblyomma scultpum nymphs or adults with the exception of one of Amblyomma parvum adult. In relation to anti-rickettsia serology to five Rickettsia species, 55.2% of pigs from commercial farms reacted to al least one species, backyard pigs reacted to 89.7% and all pigs of SISCAL showed anti-rickettsia titers. Consecutive tick sampling (June 2014 to February 2016) in SISCAL FAZU in Uberaba, showed the establishment A. sculptum ticks maintained by domestic pigs. These observations demonstrate the ability the pigs to maintain populations of A. sculptum at a favorable environment and may indicate a new trend in environmental infestations by this species of tick. Exposure to Leptospira and Rickettsia demonstrated the potential pigs exposure and transmission of important diseases in public health.